Porous biomaterial scaffolds for skeletal muscle tissue engineering - Kozan, Natalie G.; Joshi, Mrunmayi; Sicherer, Sydnee T.; Grasman, Jonathan M. (Frontiers in Bioengineering and Biotechnology, 2023)
Volumetric muscle loss is a traumatic injury which overwhelms the innate repair mechanisms of skeletal muscle and results in significant loss of muscle functionality. Tissue engineering seeks to regenerate these injuries through implantation of biomaterial scaffolds to encourage endogenous tissue formation and to restore mechanical function. Many types of scaffolds are currently being researched for this purpose. Scaffolds are typically made from either natural, synthetic, or conductive polymers, or any combination therein. A major criterion for the use of scaffolds for skeletal muscle is their porosity, which is essential for myoblast infiltration and myofiber ingrowth. In this review, we summarize the various methods of fabricating porous biomaterial scaffolds for skeletal muscle regeneration, as well as the various types of materials used to make these scaffolds. We provide guidelines for the fabrication of scaffolds based on functional requirements of skeletal muscle tissue, and discuss the general state of the field for skeletal muscle tissue engineering.